Needs analysis for developing culturally responsive teaching for remedial education: What do teachers need? - Anuas, Salehuddin Al As; Nasri, Nurfaradilla Mohamad; Alias, Aliza (Specijalna edukacija i rehabilitacija, 2023)
Introduction. Culturally responsive teaching modifies the learning experience by building an atmosphere that celebrates, acknowledges, and establishes the cultural capital that teachers and students create in the classroom. However, lessons that consider culture need to be fully proposed in remedial education. Objectives. Thus, this study views culture as one of the most significant variables to be implemented in remedial education, especially in assisting students’ mastery of literacy skills by utilizing needs analysis research for remedial teachers. Methods. The needs analysis procedure was adapted and modified by focusing on three elements: lack situation analysis, present situation analysis, and target situation analysis. Subsequently, data were collected via an online questionnaire involving 252 voluntary remedial teachers from the middle-zone state in Malaysia. Results. The present situation analysis summarizes students’ learning in remedial classrooms, indicating a considerable influence when teachers employ cultural-based learning. Nonetheless, the lack situation analysis demonstrates that teachers lack access to teaching resources, and the remedial education curriculum does not emphasize cultural-based learning. Conclusion. Target situation analysis suggests introducing culturally responsive teaching with the components of teaching, connecting, acceptance, classroom community, interaction, and evaluation as practical and wide-ranging approaches for remedial education. It is proposed that curriculum developers establish a guideline for remedial teachers in utilizing culturally responsive teaching for remedial education.
Keywords: needs analysis; remedial education; culturally responsive teaching